PENGARUH LATIHAN TIGA PEMAIN MENYUNDUL BOLA TERHADAP KEMAMPUAN HEADING SSB MITRA KANDIS - Harlin Edinton L; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstark: The problem in this research is that heading the ball often draws when the duel is in the air with the opponent, even if you are seen as losing often and less focused on heading the ball. The form of this research is (one group pretest-postest design) with a population of SSB Mitra Kandis. The data in this study related to the entire population, namely 16 subjects. The instrument used in this research was to use the head test. Based on the analysis of the normality test on the independent variable (X), it produces a LoMax of 0.164 and an L table of 0.213, which means that LoMax < Ltable. while the dependent variable (Y) returns a LoMax of 0.127 and an L table of 0.213. This means that LoMax < Ltable is normally distributed. When testing the hypothesis for the t-distribution, it can be concluded that between the variable x and the variable y the value of t = 4.464 is obtained, then tcount> ttable (4.464)> (1.753), then Ha is accepted, in other words, there is a significant effect on the training of three players heading the ball against SSB Mitra Kandis' heading ability.Key Words: Three-Player Cup Exercise, Cup Skill, Soccer